Uji Antagonis Isolat Jamur Rizosfer Lokal Terhadap Phytophthora sp. Im5 dari Pangkal Batang Tanaman Jeruk Siam (Citrus nobilis var. microcarpa) - Mukarlina, Imu Rohayatun M, Rahmawati (Jurnal Protobiont, 2017)
Fungi isolate from members of species of Phytophthora sp. Im5 is one of the pathogens that cause Brown Rot Gummosis on siam citrus plant (Citrus nobilis var. microcarpa). The control of plant pathogens is biologically done by utilizing biological agents in form of rhizosphere fungi that have antagonistic activity. This research aims to determine the antagonistic activity of rhizosphere fungi ( isolate : Mucor sp. Im1, Penicillium sp. Im2, Penicillium sp. Im3, and Trichoderma sp. Im4 ) in controlling fungi isolate of species of Phytophthora sp.Im5. Isolation, identification and antagonistic test were conducted at Microbiology Laboratory, Faculty of Mathematics and Science of Tanjungpura University Pontianak from February to June 2017. This research used Completely Randomized Design with five treatments and three replications which obtained a total of 15 experimental units. The antagonistic test used double test methods. The highest antagonistic activity in suppressing the growth of fungi isolate Phytophthora sp. Im5 is fungi isolate Mucor sp. Im1 with a percentage of 45.48%.